ANALISIS PERANCANGAN ALAT KHUSUS UNTUK PEMASANGAN SUSPENSI BELAKANG PADA UNIT HD785-7 - Rasma Rasma; Hendro Purwono; Riki Effendi (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2018)
General Overhaul (GOH) is so much on the HD785-7 unit that it requires speed, accuracy, and discipline during the process so that the target can be met. Slow speed is influenced by several factors, one of which is the process of installing rear suspension. Now the rear suspension installation process is carried out by 6 manpower using belt-shaped tools that require installation time of ± 2 hours (1 piece) so that it is considered inefficient and unsafe for mechanics. The purpose of this research is to design special tools so that the process is faster, safer, and the number of mechanics decreases. The method used in this study is Seven-Ups ++ Innovation Method so that innovation activities can run in rules and produce optimal output. The results obtained from the design of this special tool is that the rear suspension install process is only carried out by 3 manpower, is safer, and the installation time is ± 30 minutes (1 piece).